LISAM: an open source GIS-based model for liveability spatial assessment - Antognelli,Sara; Vizzari,Marco (PeerJ Preprints, 2016)
Ecosystem Services (ES) and Urban Services (US) influence place liveability in a comparable manner so that assessing landscape liveability considering both types of services can result effective for landscape planning and policy-making purposes. Considering that liveability is strongly dependent also on landscape perception by local population, stakeholder involvement results essential for a more coherent liveability assessment. In this study, a Spatial Multicriteria Decision Aiding (S-MCDA) approach guided the development of a LIveability Spatial Assessment Model (LISAM). Using a combination of GIS techniques (euclidean distance, kernel density estimation, network analysis, viewshed analysis), implemented in open-source geo-spatial software (QGIS, PostGIS and PostgreSQL), consistent and comparable ES and US spatial indices were calculated in a study area located in central Italy. These indices, according to the Analytical Hierarchy Process (AHP), were integrated with their percentage weights on liveability deriving from stakeholders interviews. Then, to investigate the liveability levels of local population, main statistics of liveability values were calculated per census section. Results include overall liveability indices at a local scale, and key statistics of liveability related to resident population. The work highlights the effectiveness of LISAM to assess local liveability and to deliver important information for policy-makers. Results show a strong, nonlinear correlation between local liveability and population density. Both the tendency to attribute higher importance to US than ES, and to the underestimation of ES quantity has emerged. The future integration in LISAM of ecosystem and urban disservices would be relevant to consider those landscape factors that reduce the overall level of place liveability.
Keywords: ecosystem services mapping; spatial multicriteria decision analysis; liveability mapping; urban services; landscape planning and management